2017
DOI: 10.1186/s40246-017-0113-7
|View full text |Cite
|
Sign up to set email alerts
|

Long non-coding RNAs as novel players in β cell function and type 1 diabetes

Abstract: BackgroundLong non-coding RNAs (lncRNAs) are a sub-class within non-coding RNA repertoire that have emerged as crucial regulators of the gene expression in various pathophysiological conditions. lncRNAs display remarkable versatility and wield their functions through interactions with RNA, DNA, or proteins. Accumulating body of evidence based on multitude studies has highlighted the role of lncRNAs in many autoimmune and inflammatory diseases, including type 1 diabetes (T1D).Main body of abstractThis review hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
41
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(41 citation statements)
references
References 99 publications
0
41
0
Order By: Relevance
“…They also affect DNA methylation, the chromatin landscape, and subsequent gene silencing or activation [8][9][10]. Abnormal expression of lncRNAs has been associated with a variety of human diseases, including diabetes [11]. Recent studies have identified thousands of lncRNAs in human pancreatic beta cells as well as in mouse pancreatic islet cells [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…They also affect DNA methylation, the chromatin landscape, and subsequent gene silencing or activation [8][9][10]. Abnormal expression of lncRNAs has been associated with a variety of human diseases, including diabetes [11]. Recent studies have identified thousands of lncRNAs in human pancreatic beta cells as well as in mouse pancreatic islet cells [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…We recently used such an approach to construct protein interaction networks from all genes located in non-HLA loci associated with T1D combined with tissue-specic transcriptomic data to identify significantly regulated network. 37 , 82, 83, 84, 85 . This indicates that protein networks can add biological context to candidate genes identified through GWAS.…”
Section: New Insights Arising From Gwasmentioning
confidence: 99%
“…84 Nevertheless, it is foreseen that a more in-depth understanding of ncRNAs may in near future open new strategies for diagnostics, classification and personalized therapeutic regiments in T1D and other immune-mediated diseases. 85 …”
Section: New Insights Arising From Gwasmentioning
confidence: 99%
See 1 more Smart Citation
“…Long noncoding RNAs (lncRNAs) constitute a group of RNA molecules more than 200 nucleotides long that are not translated into proteins. LncRNAs are associated with different diseases (9,10), including diabetes (11)(12)(13)(14), and are known to orchestrate biologically relevant (15) signaling networks that regulate cell-and tissue-specific gene expression (16)(17)(18). Recent studies have examined lncRNAs in human pancreatic islets (19)(20)(21)(22)(23); one of these landmark studies (22) uncovered human islet cell lncRNAs that are associated with key pancreatic transcription factors.…”
Section: Introductionmentioning
confidence: 99%